Spent FCC catalyst for preparing alkali-activated binders: An opportunity for a high-degree valorizatio - Tashima, M. M.; Soriano, L.; Akasaki, J. L. [UNESP]; Castaldelli, V. N. [UNESP]; Monzó, J.; Payá, J.; Borrachero, M. V. (Trans Tech Publications, 2014)
Spent FCC catalyst is a waste from the petrochemical industry which has excellent pozzolanic properties, containing more than 90% silica and alumina. Its similarity to metakaolin creates interesting prospects for its use in the production of alkali-activated binders. In this study, the alkali activation of this residue, spent FCC catalyst, through mixtures with alkali hydroxide and silicate solutions (both sodium and potassium) has been carried out. The alkali cation had an important role in the nature of AA-FCC pastes: some differences in the mass loss in the thermogravimetric tests and in the X-ray mineral characterization were found. No significant differences in compressive strength were observed for mortars cured for 3 days in several conditions: room temperature and 65°C. Prepared AA-FCC mortars had a compressive strength of about 65-70 MPa. Microstructural studies showed that an amorphous, dense and compact microstructure was obtained, independent of the activating solution and curing condition. © (2014) Trans Tech Publications, Switzerland.
Keywords: Alkali-activated binder; Compressive strength; Spent FCC catalyst; Waste valorization